QuickBundles, a Method for Tractography Simplification - Garyfallidis, Eleftherios; Brett, Matthew; Correia, Marta M.; Williams, Guy B.; Nimmo-Smith, Ian (Frontiers in Neuroscience, 2012)
Diffusion MR data sets produce large numbers of streamlines which are hard to visualize, interact with, and interpret in a clinically acceptable time scale, despite numerous proposed approaches. As a solution we present a simple, compact, tailor-made clustering algorithm, QuickBundles (QB), that overcomes the complexity of these large data sets and provides informative clusters in seconds. Each QB cluster can be represented by a single centroid streamline; collectively these centroid streamlines can be taken as an effective representation of the tractography. We provide a number of tests to show how the QB reduction has good consistency and robustness. We show how the QB reduction can help in the search for similarities across several subjects.